2015
DOI: 10.1177/0960327115601760
|View full text |Cite
|
Sign up to set email alerts
|

Skin sensitization

Abstract: Skin sensitization associated with allergic contact dermatitis is a common health problem and is an important consideration for toxicologists in safety assessment. Historically, in vivo predictive tests have been used with good success to identify substances that have the potential to induce skin sensitization, and these tests formed the basis of safety evaluation. These original tests are now being replaced gradually either by in vitro assays or by further refinements of in vivo methods such as the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 61 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…Recently, also a test battery for dermal sensitization has been approved. In this case, the three tests currently forming the battery cover key events of an adverse outcome pathway (Basketter et al 2015;Ezendam et al 2016;Reisinger et al 2015). A third successful example of in vitro test battery use, in another domain of toxicology, is the potential substitution of the in vivo uterotrophic assay of the endocrine disruptor screening program by a set of ToxCast assays directed to various steps relevant for oestrogen signalling (Browne et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, also a test battery for dermal sensitization has been approved. In this case, the three tests currently forming the battery cover key events of an adverse outcome pathway (Basketter et al 2015;Ezendam et al 2016;Reisinger et al 2015). A third successful example of in vitro test battery use, in another domain of toxicology, is the potential substitution of the in vivo uterotrophic assay of the endocrine disruptor screening program by a set of ToxCast assays directed to various steps relevant for oestrogen signalling (Browne et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Skin sensitization associated with allergic contact dermatitis (ACD) is the second most common occupational illness accounting for 10–15% of all occupational disease worldwide [ 1 ]. The disease not only impairs the quality of life for the patients but also results in high costs in healthcare systems and economy [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…111 Due to the high inter-individual variability of human tests, multiple sources of exposure must be evaluated for quantitative risk assessment of skin sensitization. 96 It has been shown that consensus prediction typically affords models of higher accuracy.…”
Section: Resultsmentioning
confidence: 99%